Protease activated receptor 1 (PAR-1) activation by thrombin is protective in human pulmonary artery endothelial cells if endothelial protein C receptor is occupied by its natural ligand - Bae, Jong-Sup; Rezaie, Alireza R (Thrombosis and haemostasis, 2008)
We recently demonstrated that the occupancy of endothelial protein C receptor (EPCR) by its natural ligand activated protein C (APC)/protein C switches the protease activated receptor 1 (PAR-1)-dependent signaling specificity of thrombin from a disruptive to a protective effect in cultured human umbilical vein endothelial cells. Given the phenotypic differences between endothelial cells in venular and arterial beds, in this study we evaluated the signaling function of thrombin in human pulmonary artery endothelial cells (HPAECs) before and after treating them with PC-S195A which lacks catalytic activity but exhibits a normal affinity for EPCR. As expected, both thrombin and thrombin receptor agonist peptide (TRAP) enhanced the permeability barrier of HPAECs; however, both PAR-1 agonists exhibited a potent barrier protective effect when the cells were treated with PC-S195A prior to stimulation by the agonists. Interestingly, similar to APC, thrombin exhibited a potent cytoprotective activity in the LPS-induced permeability and TNF-alpha-induced apoptosis and adhesion assays in the PC-S195A treated HPAECs. Treatment of HPAECs with the cholesterol depleting molecule methyl-beta-cyclodextrin eliminated the protective effect of both APC and thrombin. These results suggest that the occupancy of EPCR by its natural ligand recruits PAR-1 to a protective signaling pathway within lipid rafts of HPAECs. Based on these results we conclude that the activation of PAR-1 by thrombin would initiate a protective response in intact arterial vascular cells expressing EPCR. These findings may have important ramifications for understanding the mechanism of the participation of the vascular PAR-1 in pathophysiology of the inflammatory disorders.